2008
DOI: 10.1523/jneurosci.1926-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 Acts as a Repulsive Guidance Cue for Sensory Axonal Projections toward the Spinal Cord

Abstract: During early development, the ventral spinal cord expresses chemorepulsive signals that act on dorsal root ganglion (DRG) axons to help orient them toward the dorsolateral part of the spinal cord. However, the molecular nature of this chemorepulsion is mostly unknown. We report here that netrin-1 acts as an early ventral spinal cord-derived chemorepellent for DRG axons. In the developing mouse spinal cord, netrin-1 is expressed in the floor plate of the spinal cord, and the netrin receptor Unc5c is expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
48
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 28 publications
2
48
3
Order By: Relevance
“…Wnt/b-catenin signaling promotes sensory neurogenesis in early neural crest cells (Lee et al, 2004), while bone morphogenic protein (BMP) signals induce neural crest cells to differentiate into sympathetic neurons (Reissmann et al, 1996). Semaphorin3A, axonin-1/SC2, and netrin-1 are required as repulsive guidance cues for the formation of sensory axonal projections to the spinal cord (Masuda et al, 2003(Masuda et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Wnt/b-catenin signaling promotes sensory neurogenesis in early neural crest cells (Lee et al, 2004), while bone morphogenic protein (BMP) signals induce neural crest cells to differentiate into sympathetic neurons (Reissmann et al, 1996). Semaphorin3A, axonin-1/SC2, and netrin-1 are required as repulsive guidance cues for the formation of sensory axonal projections to the spinal cord (Masuda et al, 2003(Masuda et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 First, in the mouse embryo at embryonic day (E) 10-11.5 when many DRG axons orient themselves to reach the DREZ, netrin-1 is strongly expressed in the floor plate of the ventral spinal cord but not in the dorsal spinal cord (Fig. 1A).…”
mentioning
confidence: 99%
“…We clearly showed that netrin-1 exerts a chemorepulsive activity toward developing DRG axons and that the ventral spinal cord-derived repulsive activity depends on netrin-1 in vitro. 8 Additional evidence for a chemorepulsive role of netrin-1 came from the observation of DRG axonal trajectories in netrin-1-deficient mice. 7,8 In netrin-1-deficient embryos at E10, we showed that some DRG axons became misoriented toward the ventral spinal cord, probably because of the absence of netrin-1 proteins in the ventral spinal cord (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations